Work and organisational psychology - Boyle, Gregory J.; O'Gorman, John G.; Fogarty, Gerard J. (Sage benckmarks in Psychology., 2016)
In five thematic volumes, this collection brings together key papers on the topic of work and organizational psychology, and together with the introductory chapters written by the editor for each volume, is designed to serve the interests of psychology scholars, and also those involved in the social and behavioural sciences, more broadly.